MiR‐142‐5P regulates triglyceride by targeting CTNNB1 in goat mammary epithelial cells. Issue 5 (15th March 2020) - Sui, MeiXia; Wang, ZongWei; Xi, Dan; Wang, HanHai
Abstract: MicroRNAs (miRNAs) regulate genes through post‐transcriptional regulation by targeting the 3′‐UTR of mRNA to downregulate gene expression. Several reports have indicated that miRNA regulation can affect many physiological processes, including immune function, apoptosis, cell proliferation and differentiation, and milk fat metabolism. In this study, miR‐142‐5P promoted milk fat metabolism, and inhibition of miR‐142‐5P suppressed milk fat metabolism both in vivo and in vitro. The luciferase and Western blot assays indicated that catenin beta‐1 ( CTNNB1 ) is a potential target for miR‐142‐5P. In addition, CTNNB1 inhibited milk fat metabolism. In summary, miR‐142‐5P may promote milk fat metabolism by inhibiting CTNNB1 expression.